Beyond the Margins: The Novel of Protest and Production - Stacey Berry ([sic])
The idea expressed in the quotation above, by a hostage-poet in 1960s Beirut that appears in Don DeLillo’s novel MAO II, suggests the importance of writing as a way to produce new space. The narrative examines the difficult and necessary relationship between the writer, the written word, and the production of social change. In focusing attention specifically on the power of text to influence systems of oppression on a large cultural scale, MAO II provides examples of the ways in which texts record and respond to unique oppressive situations. In this way, the text functions more complexly within the space of the larger social dialectic than simply as a record of social failings. By presenting the violence of oppressive space back to the society that created it, the novel becomes an object of social protest. An examination of two other novels of social protest, John Edgar Wideman’s Philadelphia Fire and Sherman Alexie’s Indian Killer, further illustrates the way that the book is used as an instrument of social change. These novels present arguments about the power of writing to radically expose failures of the social dialectic that, as a consequence, create new space within that dialectic.